History and Legacy of Alan Turing for Computer Science (International Journal of Scientific Research and Management (IJSRM), 2024)
Throughout history we encounter some personalities who think ahead of their time and, in many cases, are misunderstood or even wronged. However, they all have one thing in common: they are geniuses who find impressive solutions to complex problems. This article aims to carry out, through bibliographical research using qualitative data analysis methodology, a historical review of one of the important personalities who wrote his name in history and has great relevance in the development of modern computing: Alan Mathison Turing or how it is known: Alan Turing. Considered the father of theoretical computer science and artificial intelligence, he made his great contribution to humanity by developing, in 1936, through an academic article, an automatic machine ("a-machine", which was later called the Turing), who could read and write different numbers and symbols. This article covers since his birth, covering his academic trajectory, understanding a little of his mentality and vision around machines and technological equipment, his partnerships and some interesting facts about his life. Thus, it can be understood that, even at that time, it was already possible to visualize the signs of the first computational logics and realize that machines have dynamics beyond human understanding, as they can also learn from humans and other machines and, best of all, Above all, transmit this knowledge with quality. Thus realizing the legacy and historical milestone that this British mathematician, computer scientist, philosopher and biologist left for the modern and contemporary world in which we live today.